Analisis Yuridis Dampak Over Kapasitas pada Ruang Tahanan terhadap Hak-Hak Narapidana: Studi di Lembaga Pemasyarakatan Kelas IIB Wonogiri - Dewi, Anjar Pramudita Mira; Putri, Hanuring Ayu Ardhani; Dewi, Nourma (AL-SULTHANIYAH, 2025)
To address the issue of overcrowding in correctional institutions, one of the alternative approaches is to replace imprisonment with other forms of sentencing, such as remission, conditional leave, and parole. These alternatives serve as optional punishments outside the primary criminal sanctions. This study employs an empirical juridical method with a descriptive approach. The findings reveal several key factors contributing to prison overcrowding, namely: (1) the rising crime rate; (2) the ease with which individuals are detained upon suspicion or indictment; (3) the lack of clear standard operating procedures (SOP) regarding detention postponement; (4) the underutilization of alternative punishments other than imprisonment; (5) the high rate of recidivism; and (6) the implementation of stricter remission policies for inmates convicted of corruption and narcotics-related crimes. The impacts of overcrowding in the Class IIB Correctional Facility in Wonogiri include: (1) difficulties for inmates in resting and engaging in activities; (2) obstruction of the right to file complaints; (3) inadequate sanitation; (4) limited access to proper healthcare services; (5) insufficient supervision; (6) suboptimal rehabilitation and self-reliance programs; and (7) increased potential for conflict among inmates.